3
$\begingroup$

I need to find the tangent line of the function $y=g(x)$ implicitly defined by

$(x^2+y^2)^2-2a^2(x^2-y^2)=0$

at $(0,0)$, but I don't know how.

I can't use implicit differentiation and evaluate at $(0,0)$, because when $y=0$ I can't use the Implicit Function Theorem to calculate the derivative and, therefore, the slope of the tangent line.

I'd appreciate your help.

Thanks.

$\endgroup$
0
$\begingroup$

$$(x^2+y^2)^2-2a^2(x^2-y^2)=0$$

Solving for $y$ we do substitution $t=y^2$

$$x^4+x^2t+t^2-2a^2x^2+2a^2t=0$$ $$t^2+t(2x^2+2a^2)+x^4-2a^2x^2=0$$ $$t=\pm a\sqrt{4x^2+a^2}-x^2-a^2$$

As $t=-a\sqrt{4x^2+a^2}-x^2-a^2$ is not positive we get solutions

$$y=\pm \sqrt{a\sqrt{4x^2+a^2}-x^2-a^2}$$

Let $f(x)=\sqrt{a\sqrt{4x^2+a^2}-x^2-a^2}$. We have $y=\pm f(x)$, $y'=\pm f'(x)$. The derivative of $f$ is the following

$$f'(x)=\frac{1}{2\sqrt{a\sqrt{4x^2+a^2}-x^2-a^2}}\cdot \left( a\frac{1}{2\sqrt{4x^2+a^2}}\cdot(8x)-2x \right)$$ $$=\frac{x\left(a\frac{2}{\sqrt{4x^2+a^2}}-1\right)}{\sqrt{a\sqrt{4x^2+a^2}-x^2-a^2}}$$

Function $f$ is continuous and differentiable at any small neighborhood of $0$ excluding $0$ itself. The limits of $f'(x)$ as $x\to0^\pm$ exist and they are given by

$$\lim\limits_{x\to0^+}f'(x)=1$$ $$\lim\limits_{x\to0^-}f'(x)=-1$$

Thus at $(0,0)$ there are two tangent lines with equations

$$t_1(x)=x$$ $$t_2(x)=-x$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.